Suicidal behavior in crack and alcohol users (Research, Society and Development, 2020)
Objective: to identify and compare the presence of suicidal behavior among crack and alcohol users. Method: quantitative, transversal, descriptive and analytical approach. Data collection took place through interviews with 105 patients allocated in two groups according to the psychiatric clinical diagnosis, in the Alcohol group and the Crack group. Results: Sociodemographic characteristics differed significantly between groups in relation to age (p